Exploring Multiple Religious Identities through Mixed Qualitative Methods - King, Katherine; Hemming, Peter (Fieldwork in Religion, 2012)
This article offers a reflexive account of the process of researching religious identity with young people, and considers how combining methods may enable young people to explore their own identities in different ways. Drawing upon three participant case studies it explores the public–private spectrum produced as part of discussion groups, semi-structured interviews and an innovative online e-Journal research activity. As participants moved through each stage of the research process, the way in which they represented their religious identities shifted as they encountered differing social environments, became more practised at telling their own lives, or had evolved their own perspectives over time. Employing mixed methods contributes a more nuanced understanding of the role of religion in young people’s lives yet also raises important ethical implications surrounding participant confidentiality in research.